351 Substantial lymph-vascular space invasion (LVSI) as predictor of distant relapse and poor prognosis in low-risk early stage endometrial cancer. (13th November 2020) - Tortorella, L; Restaino, S; Zannoni, G; Vizzielli, G; Chiantera, V; Cappuccio, S; Gioè, A; La Fera, E; Dinoi, G; Angelico, G; Scambia, G; Fanfani, F
Abstract : Objective: To evaluate the prognostic role of LVSI, evaluated in a semi-quantitative fashion on prognosis of early stage, low risk endometrial cancer (EC). Methods: We enrolled patients who underwent surgery for EC between 2003 and 2018 in two referral cancer center. All patients had endometrioid EC, G1-G2, with myometrial invasion <50%, and no lymph-node involvement. LVSI was analyzed in a semi-quantitative way, according to a three-tiered scoring system in absent, focal and substantial. Results: Among 524 patients, any positive LVSI was found in 57 patients (10.9%) with 6.7% (n=35) focal LVSI and 4.2% (n=22) substantial LVSI. Substantial LVSI was associated to higher rate of G2 (p<0.001), myometrial infiltration (p=0.002) and greater tumor dimensions (p=0.014). Patients with substantial LVSI were more likely to receive adjuvant treatment (6.6% vs 52.6%p<0.001). The 5-year OS was 99.5% in patients with absent LVSI and 70.6% in those with substantial LVSI (p<0.001). The 5-year recurrence free survival was 93.6% in patients with absent LVSI and 56.5% in those with substantial LVSI (p<0.001). The rate of distant failures increased from 1.8% for absent LVSI to 22.7% for substantial LVSI (p=0.002). In univariate analysis substantial LVSI was the strongest predictor of poor overall survival (HR= 11.9, p=0.001). Multivariate analysis showed that substantial LVSI was an independent predictive factor of both recurrence (HR=5.88, p=0.001) and distant failure (HR=10.6, p=0.006). Conclusions: Substantial LVSI represents the strongest independent risk factor for decreased survival and distant relapse, indicating a role for potential hematogenous dissemination.